2019
DOI: 10.1002/aet2.10397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gender Differences in Ultrasound Milestone Evaluations During Emergency Medicine Residency Training: A Multicenter Study

Abstract: Objectives: Prior literature has demonstrated incongruities among faculty evaluation of male and female residents' procedural competency during residency training. There are no known studies investigating gender differences in the assessment of procedural skills among emergency medicine (EM) residents, such as those required by ultrasound. The objective of this study was to determine if there are significant gender differences in ultrasound milestone evaluations during EM residency training. Methods:We used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 13 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Five were excluded based on study objectives, 23–27 four for study design, 28–31 one because it was a duplicate, 32 and one for not including EM residents 33 . Ten records underwent data extraction 12,15,32,34–40 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five were excluded based on study objectives, 23–27 four for study design, 28–31 one because it was a duplicate, 32 and one for not including EM residents 33 . Ten records underwent data extraction 12,15,32,34–40 …”
Section: Resultsmentioning
confidence: 99%
“…A summary of each study's main findings is outlined in Table 2. Seven of the 10 studies examined assessments based on the Accreditation Council for Graduate Medical Education (ACGME) EM or PEM milestones 12,15,32,35–37,39,40 . Four studies investigated and reported the impact of assessor gender on resident performance scores, and none of the studies reported a statistically significant difference in scores between female and male assessors 15,32,34,37 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations